2014
DOI: 10.1007/s00167-014-2963-z
|View full text |Cite
|
Sign up to set email alerts
|

Variability of landmark acquisition affects tunnel calculation in image-free ACL navigation

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…These findings confirmed the variability of tunnel positioning described several years ago by Kohn et al [58]. Shafizadeh et al [130] also analysed the variability in landmarks acquisition asking thirteen experienced surgeons to identify the bony landmark required for image-free ACL navigation in the same cadaver knee. The mean variability (SD) was 3.0 mm for the tibial landmark positions and 2.9 mm for the femoral one.…”
Section: Navigation and Tunnel Placementsupporting
confidence: 77%
“…These findings confirmed the variability of tunnel positioning described several years ago by Kohn et al [58]. Shafizadeh et al [130] also analysed the variability in landmarks acquisition asking thirteen experienced surgeons to identify the bony landmark required for image-free ACL navigation in the same cadaver knee. The mean variability (SD) was 3.0 mm for the tibial landmark positions and 2.9 mm for the femoral one.…”
Section: Navigation and Tunnel Placementsupporting
confidence: 77%
“…Tsukada et al, 25 for example, found that the utility of bony landmarks is limited in anatomic reconstruction. Shafizadeh et al 22 demonstrated that there was a great variation among experienced ACL surgeons (>50 reconstructions/y) in identifying the landmarks for tunnel position. If drilling the 2 tunnels relied solely on bony landmarks regardless of the footprint and remnant variations, we may not be able to duplicate the native footprint, arrangements, and fiber directions in all cases (particularly in the PL bundle), which may result in unsatisfactory clinical results in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies 1,11,27,28 have even found more cases of earlier procedure failure or PL bundle rerupture in DB-ACLR during second-look procedures or postoperative magnetic resonance imaging (MRI) scanning. Given that there are numerous variations in ACL footprints and arrangements in addition to the AM/PL pattern 15,24 and that the relationship between bony landmark and footprint is controversial, 22,23,25 it is possible that the BL technique may not cover the majority of the original ACL footprint if they are not in the AM/PL or reverse PM/AL arrangement pattern. Those DB-reconstructed grafts that do not match the individual native anatomy may cause more impingement compared with SB-reconstructed grafts, thus affecting clinical outcomes.…”
mentioning
confidence: 99%
“…The crucial point to note is that most ACLR researchers suggest the availability of navigation based on accuracy of drilled tunnel insertion point and precision of the surgeon drilling the tunnels [30]. Compared to a conventional method, such as the transtibial technique, anatomical reconstruction techniques hold more risks including (1) short femoral tunnel, (2) posterior wall blowout, and (3) iatrogenic damage to the cartilage of the medial femoral condyle [21] by a more horizontal direction of the femoral tunnel in three‐dimensional planes [1, 29].…”
Section: Introductionmentioning
confidence: 99%